Hand-held echocardiography during complex electrophysiologic procedures - Selda Murat; Taner Ulus; Ahmet Serdar Yılmaz; Halit Emre Yalvaç; Ezgi Çamlı; Muhammet Dural (Journal of Cardiovascular and Thoracic Research, 2023)
Introduction: Complex electrophysiologic (EP) procedures are time consuming and open to complications. Accurate and rapid recognition of cardiac pathologies is essential before, during, and immediately after such procedures. In this study, we aimed to compare hand-held echocardiography (HHE) with standard echocardiography (SE) to determine whether HHE can be used as a practical and reliable diagnostic tool during such procedures. Methods: One hundred consecutive patients undergoing complex EP procedures and catheter ablation were included in the study. All patients were evaluated with SE or HHE in terms of main cardiac pathologies at the beginning and immediately after the procedure. The diagnostic accuracy and evaluation time of both methods were compared at the beginning and after the procedure. The agreement between both methods was calculated. Results: At the beginning and after the procedure, opening and evaluation times with HHE were significantly shorter than with SE (P<0.001 for all). There was significant agreement between the two methods in the diagnosis of cardiac pathologies (Agreement was 95% for minimal mild aortic regurgitation (AR), 99% for moderate/ severe AR, 93% for minimal/ mild mitral regurgitation (MR), 95% for moderate/ severe MR, 100% for pericardial effusion, and 100% for left ventricular thrombus at the beginning of the procedure). Conclusion: With the use of HHE during complex EP procedures, cardiac pathologies can be diagnosed with similar accuracy as SE. In addition, HHE has a significant advantage over SE in terms of time to diagnosis.